Absence of Evidence for the Participation of the Macrophage Cellular Prion Protein in Infection with Brucella suis - Fontes, Pascaline (American Society for Microbiology, 2005)
Brucella spp. are stealthy bacteria that enter host cells without major perturbation. The molecular mechanism involved is still poorly understood, although numerous studies have been published on this subject. Recently, it was reported that Brucella abortus utilizes cellular prion protein (PrP(C)) to enter the cells and to reach its replicative niche. The molecular mechanisms involved were not clearly defined, prompting us to analyze this process using blocking antibodies against PrP(C). However, the behavior of Brucella during cellular infection under these conditions was not modified. In a next step, the behavior of Brucella in macrophages lacking the prion gene and the infection of mice knocked out for the prion gene were studied. We observed no difference from results obtained with the wild-type control. Although some contacts between PrP(C) and Brucella were observed on the surface of the cells by using confocal microscopy, we could not show that Brucella specifically bound recombinant PrP(C). Therefore, we concluded from our results that prion protein (PrP(C)) was not involved in Brucella infection.